Japanese students' interaction using smartphone apps: a study of young learners in a private high school - Jason Somerville (Institut Agama Islam Negeri Palopo, 2019)
The widespread use of mobile devices plays a significant role in our everyday lives and has changed the way we communicate and interact. Mobile-Assisted Language Learning (MALL) offers numerous opportunities for learning inside the classroom with mobile devices no longer seen as only social and gaming devices. Research shows that mobile device applications (apps) are now valuable tools which are used for education and language learning, in particular for promoting learner collaboration and social interaction. The purpose of this study is to discover how smartphones and apps can support greater student interaction. With an increased number of educational institutions, namely private junior and senior high schools in Japan embracing mobile technology into classroom pedagogy, this study investigates which smartphone repurposed apps are useful for encouraging interaction between students. The significance of this research is beneficial for learners, teacher-educators and app developers in advancing the benefits of social interaction in second language acquisition (SLA) utilising mobile devices. Through qualitative structured observation of participants in a Tokyo high school classroom, this study explores which smartphone apps are the most successful in encouraging interaction measured by frequency counts. The quantitative data reveal which apps are the most suitable for supporting greater social interaction and collaboration between learners. The implications derived from the findings support the argument that smartphones provide increased student-student interaction and collaboration.